Topical Problems in Pedagogical Activity - Zokirovich, Makulov Shuxrat (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes the existing problems in the field of pedagogical activity. Taking into account the complexity of pedagogical activity, the author offers a solution to the problem.